Pathological fracture due to primary bone lymphoma in a patient with a history of prostate cancer: A case report and review of literature - Bhakta, Pooja; Hunzeker, Zachary E.; Garcia, Juan D.; Youssef, Ayman; Grant, Bradley J.; Alfattal, Rasha; Weaver, Dylan; Bhargava, Peeyush; Rischall, Ariel; Musunuru, Tejo; Muthukumarana, Palawinnage V.; Mallick, Jayati; et al. (Frontiers in Oncology, 2023)
Primary bone lymphoma (PBL) is a rare extranodal presentation within lymphomas and primary bone malignancies. Pathologic fracture (PF) is a common complication of metastatic bone disease but is rarely the presentation of a primary bone tumor. We report a case of an 83-year-old male with a history of untreated prostate cancer, presenting with atraumatic fracture of his left femur after months of intermittent pains and weight loss. Radiographic workup revealed a lytic lesion suspicious for PF secondary to metastatic prostate cancer, however initial core biopsy results were inconclusive for malignancy. A complete blood count with differential and complete metabolic panel were within normal limits. During surgical fixation and nailing of the femur, a reaming biopsy was performed as a repeat measure and revealed a finding of diffuse large B-cell lymphoma (DLBCL). Staging with positron emission tomography and computed tomography (PET-CT) found no evidence of lymphatic or visceral involvement and chemotherapy was promptly initiated. This case highlights the diagnostic workup challenges for PF secondary to PBL, especially in the setting of concurrent malignancy. Due to the nonspecific presentation of a lytic lesion on imaging associated with atraumatic fracture, we highlight PBL as an important diagnostic consideration.